IMPLEMENTATION OF PROPORTIONALITY PRINCIPLE IN ABORTION CRIMINALIZATION: BALANCING PUBLIC AND PRIVATE INTERESTS - Шевченко, Сніжана Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Objective: to analyze the implementation of proportionality principle as the principle of balancing of public and private interests in abortion criminalization. Research methods: analytical, axiological, comparative-legal and others. Results: it is identified and critically overviewed main approaches to determine public and private interests in abortion criminalization. Discussion: it is argued that no public interest in abortion criminalization can be justified in imposing disproportionate restrictions on privacy right of a woman or in creating conditions under which privacy right will be abused. Establishment of criminal responsibility for abortion is a reflection of particular outlook and its extrapolation into law. Abortion criminalization is ultimately nothing more than a choice of ideological solution to ethical dilemma of establishing a state restriction on access to abortion or a complete ban on abortion. Criminalization is the ultimate remedium power of state to regulate public relations which means that if certain relationships can be settled not by criminal measures but by any others which is less burdensome for human rights then the legislator must do so. Thus, it seems logical to conclude that within the framework of the classification approach, the individual components of the principle of proportionality are fragmented and detailed. This leads us to the conclusion that defining the principle of proportionality as an integral principle does not seem to be what is not expedient but impossible because of the formal laws of logic. Given this, let the author assert that it is the principle of proportionality that is the only fundamental basis of criminalization as a process and the subsystem of principles proposed by scientists it is not principles at all. It rather can be regarded as rules arising from the principle of proportionality. The state of research about the system of criminalization principles in the domestic doctrine of law is largely determined by the researches that were developed in the Soviet doctrine of law. Taking the above mentioned into consideration, the task of the modern criminal law doctrine is rethink critically the Soviet doctrine of law and to go beyond the boundaries of the "coordinate system" outlined by this doctrine in studies of this problem. The application of classification approach in criminal law researches on the implementation of the principles of criminalization in the process of establishing a specific criminal law prohibition seems not to be conservative but rather archaic. Giving due respect and honor to the research of previous generations of scientists in the criminal law doctrine, the author believe that this approach does not correspond to the new challenges and tasks that criminal law should be aimed to resolve, for instance, the effective protection of human rights.